Intersecting Threats of Conflict, Climate Variability, and Psychosocial Stress: A Gendered Analysis of Agricultural Development and Food Security in Niger State, Nigeria - Ogheneovo, UGBOSU Seth; Christopher, ONOSEMUODE; Ogagayere-Osagie, Lucky Omamuzo (Asian Journal of Advanced Research and Reports, 2025)
Agricultural development and food security in Nigeria are increasingly undermined by the converging pressures of climate variability, escalating rural insecurity, and psychosocial stressors, particularly in conflict-prone agrarian regions. Niger State, a key food-producing area, faces recurrent farmer–herder conflicts, erratic rainfall, and extreme weather events, all of which disrupt production cycles and threaten livelihoods. This study investigates the intersecting impacts of these threats through a gendered lens, highlighting both material and psychosocial dimensions. A mixed-methods design was employed, combining quantitative surveys with qualitative key informant interviews and focus group discussions. The quantitative component involved a stratified random sample of 420 male and female farmers drawn from 12 communities selected for high exposure to both conflict and climate-related hazards. Data collection was conducted using structured questionnaires, which captured gender-disaggregated information on farm access, yield changes, climate experiences, and psychosocial well-being. Descriptive statistics, chi-square tests, and logistic regression were applied to assess relationships between security, climatic, and psychosocial variables, while thematic analysis was used to synthesize qualitative narratives. Results show that farmer–herder conflicts and climate variability jointly reduced crop yields by an average of 27% and limited farm access for 61% of respondents. Psychosocial stressors, such as fear of attack, displacement trauma, and loss of social cohesion significantly reduced agricultural participation, with women reporting 34% higher levels of livelihood-related anxiety than men. Gender disparities were evident in coping strategies, resource access, and decision-making autonomy. The findings emphasize the urgent need for integrated, gender-responsive interventions that combine climate adaptation, rural security, mental health support, and equitable resource allocation to strengthen food systems in Nigeria’s conflict-affected agricultural zones.